2010
DOI: 10.1007/s00330-010-1839-y
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to low-dose radiation and the risk of breast cancer among women with a familial or genetic predisposition: a meta-analysis

Abstract: Low-dose radiation increases breast cancer risk among high-risk women. When using low-dose radiation among high-risk women, a careful approach is needed, by means of reducing repeated exposure, avoidance of exposure at a younger age and using non-ionising screening techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 46 publications
3
37
0
1
Order By: Relevance
“…The study data provide some support for omitting mammography in BRCA1 mutation carriers younger than 40, although mammographic prescreening of women in our studies may have reduced incident mammographic detection. This would comply with recommendations from studies reporting increased breast cancer risk in mutation carriers following exposure to diagnostic radiation at younger age, specifically before the age of 30 (28,29). The simulations confirmed that for BRCA1/2 mutation carriers, screening with MRI is a valuable addition to mammography screening, especially by detecting more T1A/B tumors.…”
Section: Discussionsupporting
confidence: 65%
“…The study data provide some support for omitting mammography in BRCA1 mutation carriers younger than 40, although mammographic prescreening of women in our studies may have reduced incident mammographic detection. This would comply with recommendations from studies reporting increased breast cancer risk in mutation carriers following exposure to diagnostic radiation at younger age, specifically before the age of 30 (28,29). The simulations confirmed that for BRCA1/2 mutation carriers, screening with MRI is a valuable addition to mammography screening, especially by detecting more T1A/B tumors.…”
Section: Discussionsupporting
confidence: 65%
“…1,2 The results effectively rule out the 1.8-fold relative risk estimated for .5 exposures from the Dutch meta-analysis, 3 as this estimate lies outside the 95% confidence intervals obtained here. Although our study is not powered to detect smaller effects, there is reassurance that females undergoing mammograms in their early 30s do not have a greatly increased risk of radiation-induced breast cancers.…”
Section: Discussionsupporting
confidence: 43%
“…Exposure before the age of 20 years (OR 5 2.0, 95% CI: 1.3-3.1) or a mean of $5 exposures (OR 5 1.8, 95% CI: 1.1-3.0) was significantly associated with higher breast cancer risk and the authors concluded that a careful approach is needed when using low-dose radiation on high-risk females. 3 One study suggested using single-view mammography to detect calcifications in those undergoing MRI screening. 4 Although MRI is widely advocated in some countries in females with lifetime risks as low as 20-25%, 5 in many countries, its use is limited by cost and availability.…”
Section: Introductionmentioning
confidence: 99%
“…Low-dose radiation increased breast cancer risk among high-risk women with familial or genetic aggregation of breast cancer (OR = 1.3, 95% CI 0.9-1.8), and an exposure before age 20 (OR = 2.0, 95% CI 1.3-3.1) or a mean of ≥ 5 exposures (OR = 1.8, 95% 95% CI 1.1-3.0) was significantly associated with a higher radiation-induced breast cancer [256]. A study investigating whether women with a genetic predisposition to breast cancer may be at increased risk of cancer after exposure to ionizing radiation because of exposure to mammography found that in women with BRCA1 and BRCA2 mutations it is not associated with an increased risk of breast cancer [257].…”
Section: Ionizing Radiationmentioning
confidence: 99%